Physicochemical Properties of Composite Flour Based on Rice, Sweet Potato, Potatoes, Soybean and Xanthan Gum - Rizqa Amalia; Elisa Julianti; Ridwansyah Ridwansyah (Jurnal Rekayasa Pangan dan Pertanian, 2014)
The research was aimed to study the physicochemical properties of composite flour from rice, sweet potato, potato starch and soy flours. The reseach had been performed using factorial completely randomized design, with one factor i.e the ratio of : rice flour, sweet potato flour, potato starch, soy flour and xanthan gum (T): 30%:50%:15%:4,5%:0,5%, 30%:45%:20%:4,5%:0,5%, 30%:40%:25%:4,5%:0,5%, 30%:45%:15%:9,5%:0,5%, 30%:40%:20%:9,5%:0,5%, 30%:35%:25%:9,5%:0,5%, 30%:40%:15%:14,5%:0,5%, 30%:35%:20%:14,5%:0,5%, 30%:30%:25%:14,5%:0,5%, 100%. Parameters analyzed were water content, ash content, protein content, fat content, fiber content, and color. The results showed that the ratio of rice flour, sweet potato flour, potato starch, soy flour and xanthan gum had highly significant effect on water content, ash content, protein content, fat content, fiber content, and color. Ratio of 30%: 35%: 20%: 14,5%: 0,5% had a physicochemical properties near to wheat flour therefore can be used as a wheat flour alternative in gluten free food products. Keyword : Rice flour, sweet potato flour, potato starch, soy flour, xanthan gum